Effects of reversible cognitive frailty on disability, quality of life, depression, and hospitalization: a prospective cohort study. (3rd October 2022) - Wang, Wenyu; Si, Huaxin; Yu, Ruby; Qiao, Xiaoxia; Jin, Yaru; Ji, Lili; Liu, Qinqin; Bian, Yanhui; Yu, Jiaqi; Wang, Cuili
Abstract: Objectives: Cognitive frailty, a potentially reversible condition describing the concurrence of physical frailty and mild cognitive impairment (MCI), has been recently proposed to incorporate subjective cognitive decline (SCD), a reversible pre-MCI state with more readily available cognitive reserve, as well as pre-physical frailty. Reversible cognitive frailty has been associated with dementia and mortality. We aimed to examine the association of reversible cognitive frailty with other adverse outcomes including disability, poor quality of life (QOL), depression, and hospitalization. Methods: This was a cohort study with 1-year follow-up among 735 Chinese community-dwelling older adults with intact cognition. Reversible cognitive frailty was operationalized with the presence of pre-physical or physical frailty identified by the Frailty Phenotype and SCD identified by the simplified SCD questionnaire including four self-report cognitive domains of memory, naming, orientation, and mathematical reasoning. Adverse outcomes included incident Activities of Daily Living (ADL)-Instrumental ADL (IADL) disability, poor physical, mental and overall QOL, depression, and hospitalization over 1-year follow-up. Results: The prevalence of reversible cognitive frailty was 27.8%. Participants with reversible cognitive frailty had higher risk of the incidence of ADL-IADL disability, poor physical QOL, poor mental QOL, poor overall QOL, and depression (Odds Ratios: 1.67–4.38, P  < 0.05), but not higher risk of hospitalization over 1-year follow-up. Conclusion: Reversible cognitive frailty was not uncommon and associated with incident disability, poor QOL, and depression among community-dwelling older adults. Early identification of reversible cognitive frailty can facilitate targeted interventions and may promote independence in older adults. Supplemental data for this article is available online at http://dx.doi.org/10.1080/13607863.2021.2011835